Peptidoglycan-associated outer membrane protein Mep45 of rumen anaerobe Selenomonas ruminantium forms a non-specific diffusion pore via its C-terminal transmembrane domain. Issue 10 (2nd October 2016) - Kojima, Seiji; Hayashi, Kanako; Tochigi, Saeko; Kusano, Tomonobu; Kaneko, Jun; Kamio, Yoshiyuki
Abstract: The major outer membrane protein Mep45 of Selenomonas ruminantium, an anaerobic Gram-negative bacterium, comprises two distinct domains: the N-terminal S-layer homologous (SLH) domain that protrudes into the periplasm and binds to peptidoglycan, and the remaining C-terminal transmembrane domain, whose function has been unknown. Here, we solubilized and purified Mep45 and characterized its function using proteoliposomes reconstituted with Mep45. We found that Mep45 forms a nonspecific diffusion channel via its C-terminal region. The channel was permeable to solutes smaller than a molecular weight of roughly 600, and the estimated pore radius was 0.58 nm. Truncation of the SLH domain did not affect the channel property. On the basis of the fact that Mep45 is the most abundant outer membrane protein in S. ruminantium, we conclude that Mep45 serves as a main pathway through which small solutes diffuse across the outer membrane of this bacterium. Graphical abstract: : Schematic representation of Mep45 in the outer membrane of S. ruminantium . The C-terminal region of Mep45 forms a non-specific diffusion channel.